Rheological properties of ground tyre rubber based thermoplastic elastomeric blends - Lima, Paulo
This work analyses the rheological behaviour of thermoplastic elastomeric blends (TPE) based on ground tyre rubber (GTR), more specifically the rheological behaviour of binary and ternary polypropylene (PP) based blends with different rubber materials: an ethylene propylene diene monomer (EPDM), an ethylene propylene rubber (EPR) and GTR. The study was developed under steady-shear rate conditions by capillary rheometry at three different temperatures. Time Temperature Superposition Principle (TTSP) was applied to the viscosity curves using a temperature dependent shift factor, allowing the construction of master curves for the analysed blends. The Cross-WLF model was used to predict the theological parameters, giving numerical results for viscosity similar to the experimental data. GTR increased the blends viscosity. EPR showed rheological behaviour similar to PP, and EPDM presented higher power law behaviour. Pseudoplastic behaviour was observed for all the analysed blends. Incorporation of GTR in TPE blends for injection moulding purposes was found to be a feasible strategy to upcycle this type of potentially wasted material. (C) 2015 Elsevier Ltd. All rights reserved.